PELATIHAN PENCATATAN KEUANGAN MENGGUNAKAN APLIKASI SiAPIK PADA UD BITATA FOOD BANDA ACEH - Hamdani Hamdani; Thasrif Murhadi; Saiful Bahgia (Community Development Journal : Jurnal Pengabdian Masyarakat, 2021)
Community Service Activities (PkM) which are oriented towards achieving output to increase the capacity of UD Bitata Food Banda Aceh's MSMEs in the financial aspect have shown satisfactory results. The problem of financial statements has long been a classic problem for MSMEs and has even placed it as the main problem for MSMEs. The purpose of this service is that universities are scientific institutions and educational services to provide the widest possible benefits to the community by increasing the capacity of the subjects of service. The method applied to this service is training. This method was chosen based on the needs, abilities, and academic considerations of dedication to create the solutions expected by UD Bitata Food. As a result of the training, participants have gained basic knowledge about business finance which has never been prepared according to standards. The knowledge of the trainees was measured by the results of post-training interviews. In addition, the subject has also been able to register his business to get a SiApik account which is used for recording business finances on an ongoing basis. Meanwhile, participants who were trained to become SiApik account operators have been able to input data according to the menu provided, just like compiling a business financial report. Although this service has achieved satisfactory results for both parties, the sustainability of this program is still continued with a pattern of mentoring and mentoring.